1992
DOI: 10.1161/01.str.23.9.1225
|View full text |Cite
|
Sign up to set email alerts
|

Dementia associated with lacunar infarction.

Abstract: Background and Purpose: The purpose of this study was to assess the number of patients with lacunar lesions who develop dementia and to evaluate in patients with and without dementia the relevance of risk factors for cerebrovascular disease, the occurrence of leukoaraiosis, the volume and location of vascular lesions, the size of ventricular and subarachnoid spaces, and stroke recurrence.Methods: One hundred eight patients in whom computed tomograms revealed lacunar lesions that could account for their clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
110
3
4

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(127 citation statements)
references
References 35 publications
10
110
3
4
Order By: Relevance
“…The prevalence of dementia in ischemic stroke patients is nine times higher than controls at 3 months (1) and 4 -12 times higher than in controls at 4 years after a lacunar infarct (2). Many of these dementias developed progressively, and cerebral damage is believed to be the direct cause of cognitive decline in only half of these cases (3).…”
Section: From the Departments Of ‡Pharmacology And Neuroscience And §mentioning
confidence: 99%
“…The prevalence of dementia in ischemic stroke patients is nine times higher than controls at 3 months (1) and 4 -12 times higher than in controls at 4 years after a lacunar infarct (2). Many of these dementias developed progressively, and cerebral damage is believed to be the direct cause of cognitive decline in only half of these cases (3).…”
Section: From the Departments Of ‡Pharmacology And Neuroscience And §mentioning
confidence: 99%
“…Moreover, subjects with subcortical vascular disease are at increased risk for developing dementia [6][7][8]11,18,25,28,35,36,39]. Clinicopathological studies have found that, for any level of cognitive deficit, the density of neuritic plaques and neurofibrillary tangles in the neocortex is Du 4 significantly lower in cases of AD mixed with cerebrovascular disease than in cases of AD without cerebrovascular disease [32,35,40], suggesting that cerebrovascular disease has effects in addition to AD pathology on cognition.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of vascular dementia (VaD) attributed to SIVD ranges from 36 to 50%, with higher rates noted among African Americans 1 and Asian Americans 2 than whites. 3,4 A few studies report risk of dementia to be higher among subjects with lacunar infarcts versus other subtypes of stroke, 4 and among patients with AD with concomitant lacunar versus large-artery infarcts. 5 Thus, SIVD is an important subtype of VaD either alone or in combination with AD.…”
mentioning
confidence: 99%